Empat Wajah Kekuasaan: Kajian Spektrum Kepemimpinan Politik Indonesia Pascareformasi (1999–2024) - Novita Wulandari; Aris Munandar; Renny Candradewi; Supardi Supardi (PERSPEKTIF, 2026)
This study develops a Spectrum Model of Indonesian Political Leadership through an analysis of the political thought and exercise of power of four post-reform presidents: Abdurrahman Wahid, Susilo Bambang Yudhoyono, Joko Widodo, and Prabowo Subianto. The study aims to map variations in political leadership within Indonesia’s electoral democracy from 1999 to 2024 and to explain their implications for democratic quality. Using content analysis, the research examines 86 state speeches, 24 policy documents, and 212 national media articles. The analysis employs frequency coding of key thematic terms representing orientations toward power and democracy. The findings identify four ideal types of political leadership: Normative–Pluralist, Rational–Stable, Populist–Pragmatic, and Militaristic–Adaptive. These types exhibit fundamental differences in power orientation, state–society relations, and strategies of political consolidation. The spectrum model offers a new analytical framework for understanding leadership dynamics in electoral democracies that are vulnerable to oligarchic influence and power centralization. Policy implications underscore the importance of strengthening non-executive